Non-Destructive Testing of Aluminum Alloys by Using Miniature Eddy-Current Flaw Transducers - Polyakov V. V.; Dmitriev S. F.; Ishkov A. V.; Kolubaev Е. А. Evgeny Aleksandrovich; Malikov V. N. (Diagnostics and Engineering of Novel Materials, 2014)
Title screen